Pathological evaluation of the staging axillary lymph nodes for breast cancer: a national survey in the United Kingdom. Issue 5 (5th August 2014) - Verma, Rashmi; Sundara Rajan, Sreekumar; Verghese, Eldo T; Horgan, Kieran; Hanby, Andrew M; Lane, Sally
Abstract : Aims: The handling and examination of sentinel lymph nodes (SLNs) to detect metastasis is critical in the assessment of early breast cancer patients. This survey investigates the variation in practise followed by pathology units across the United Kingdom in the staging evaluation of axillary lymph nodes (ALNs). Methods and results: A structured questionnaire, approved by the National Health Service Breast Screening Programme pathology Big 18 committee, was circulated among all pathologists. There were 160 respondents; 92% performed SLN biopsy for staging, 97% had a protocol for processing SLNs and most laboratories examined the ALNs using formalin‐fixed, paraffin‐embedded (FFPE) samples (85.6%). A few used PCR (7.5%), frozen section (3.8%) or touch imprint cytology (3.1%), with or without subsequent FFPE section examination. Currently, 33% perform serial sectioning, with the majority of the rest (75%) staining three levels using H&E. Most units (85%) undertook immunohistochemistry evaluation only when suspicious cells were detected on H&E‐stained sections. Conclusions: The range of practise in UK histopathology departments is described with regard to the dissection and evaluation of ALNs/SLN biopsy. The variation in practise was not very marked and most departments adhered to national guidelines. Any UK study seeking to relate ALN status and outcome would need to be mindful of the variability in nodal processing and examination.